Advanced photo-annealing of indium zinc oxide films for thin-film transistors using pulse UV light. Issue 1 (2nd January 2016) - Park, Sang Cheol; Kim, Dongwook; Shin, Hyunji; Lee, Do Kyoung; Zhang, Xue; Park, Jaehoon; Choi, Jong Sun
Abstract : An ultra-fast and simple method for forming high-performance metal oxide semiconductor by a solution process based on sol–gel condensation in ambient air using pulse ultraviolet-light annealing is proposed for the thin-film transistor (TFT) application. Even a small amount of light absorbance by the transparent metal oxide film provide sufficient energy to carry out sol–gel condensation because of the extremely high peak energy and broad irradiation spectrum of the xenon lamp used in this study. The fabricated indium zinc oxide TFTs had a field-effect mobility of 2.4 cm 2 V −1 s −1, which is comparable to a device performance of 2.7 cm 2 V −1 s −1 obtained through thermal annealing.